Good Bye, Lenin!, good bye to identity? - Wittenberg, Stela (Revista de Filología Alemana, 2011)
My article will be divided into three sections: the first will make a series of reflections on the relationship between the individual and society in order to approach the topic of individual and collective memory as the general framework of my work. The second, entitled “The strength of slogans”, analyses Hirschman’s work in relation to the historical events of 1989 that led to the fall of the Berlin Wall and the changes in the political identity of the former German Democratic Republic. The third section (“Memory and Identity”) focuses on the analysis of the film Good Bye Lenin! and on the transformations to the collective identity undergone by the inhabitants of the former GDR.